National Study of Innovative and Promising Programs for Women Offenders, 1994-1995 - Morash, Merry ([Verlag nicht ermittelbar], 2000)
The purpose of this study was to conduct a national-scale evaluation of correctional facilities housing female offenders in order to assess the effectiveness of current programs, including alternative sanctions and treatment programs, and management practices. The goal was to gather information on "what works for which women" with respect to the program characteristics most related to positive outcomes. The first stage of the study consisted of gathering the opinions of administrators in state departments of corrections, including state-level administrators and administrators in institutions for women (Part 1). Administrators from jails that housed women were also interviewed (Part 2). Data collected for Parts 1 and 2 focused on attitudes toward the influx of women into jails and prisons, the needs of incarcerated women, and management and program approaches for meeting those needs. Respondents were asked to identify programs that in their view stood out as especially effective in meeting the needs of incarcerated women. From this list of nominated programs, researchers conducted 62 in-depth telephone interviews with administrators of programs located in jails, prisons, and the community (Part 3). A supplement to this study consisted of telephone interviews with 11 program directors who headed mental health programs that appeared to be "state of the art" for incarcerated women (Part 4). Variables in Parts 1-4 that concern the nominated programs include the underlying principles guiding the programs, whom the programs targeted, what types of staff were employed by the programs, the most positive effects of the programs, and whether program evaluations had been completed. Program effort variables found in Parts 1-4 cover whether the programs focused on trying to treat substance abuse, stop child abuse, provide women with nontraditional job skills, parenting skills, HIV/AIDS education, and life skills, change cognitive thinking, and/or promote self-esteem. Several variables common to Parts 1-3 include whether the programs provided women with follow-up/transitional help, helped to stimulate pre-release planning, allowed visits between women and children, or used ex-offenders, ex-substance users, volunteers, or outside community groups to work with the women. Variables focusing on the types of assessment tools used cover medical assessments, VD screening, reading/math ability screening, mental health screening, substance abuse screening, needs regarding children screening, and victim-spouse abuse screening. Variables pertaining to institution management include background knowledge needed to manage a facility, the types of management styles used for managing female offenders, security and other operational issues, problems with cross-sex supervision, and handling complaints. Similar variables across Parts 1, 2, and 4 deal with the impact of private or state funding, such as respondents' views on the positive and negative outcomes of privatization and of using state services. Both Parts 1 and 2 contain information on respondents' views regarding the unique needs of women offenders, which programs were especially for women, and which program needs were more serious than others. Planning variables in Parts 1 and 2 include whether there were plans to have institutions link with other state agencies, and which programs were most in need of expansion. Further common variables concerned the influx of women in prison, including how administrators were dealing with the increasing number of women offenders, whether the facilities were originally designed for women, how the facilities adapted for women, and the number of women currently in the facilities. In addition, Part 1 contains unique variables on alternative, intermediate sanction options for women, such as the percentage of women sent to day supervision/treatment and sent to work release centers, why it was possible to use intermediate sanctions, and how decisions were made to use intermediate sanctions. Variables dealing with funding and the provision of services to women include the type of private contractor or government agency that provided drug treatment, academic services, and vocational services to women, and the nature of the medical and food services provided to women. Variables unique to Part 2 pertain to the type of offender the jail housed, including whether the jurisdiction had a separate facility for pretrial or sentenced offenders, the total rated capacity of the jail, the average daily population of pretrial females, whether the jail was currently housing state inmates, and the impact on local inmates of being housed with state inmates. Variables concerning classification and assessment focused on the purpose of the classification process for female offenders, whether the classification process was different for male and female offenders, and a description of the process used. Variables specific to Part 3 deal with characteristics of the participants, such as whether program participants were involved in a case management system, the approximate number of women and men participating in the programs, whether offenders were tried and awaiting sentence or were on probation, and the number of hours a week that individuals participated in the program. Program structure variables include whether the program was culture- or gender-specific, restrictions on program participants, and who established the restrictions. Programming strategy variables cover identifying strategies used for meeting the needs of women offenders with short sentences, strategies for women with long sentences, and what stood in the way of greater use of intermediate sanctions. Part 4 contains variables on the size of the mental health program/unit, including the number of beds in the mental health unit, the number of beds set aside for different types of diagnoses, and the number of women served annually. Diagnosis variables provide information on who was responsible for screening women for mental health needs, whether women were re-evaluated at any time other than at intake, and the most common mental health problems of women in the unit. Variables on running the program include whether the program/unit worked with private or public hospitals, the factors that hindered coordination of services among local or state facilities, the types of services affected by budget constraints, and the strategies used to prevent women from harming themselves and others. Staffing variables cover the number of psychologists, social workers, nurses, and correctional officers that worked in the mental health unit. Demographic variables were similar for all four data files. These include the institution level, the type of respondent interviewed, respondents' gender and educational background, and the number of years they had been in their positions, were employed in corrections, and had worked in women's facilities.